Seasonal pattern of tick load in Bunaji cattle in the subhumid zone of Nigeria - Bayer, W.; Maina, J.A. (Elsevier, 1984)
The seasonal pattern of tick load on Bunaji cattle under traditional management in northern Nigeria was observed over 12 months to investigate the possibilities of strategic use of acaricide. Ticks were removed 2-3 times weekly by hand from 16 animals, counted and the species determined. Tick load was low in the dry season (2-5 ticks per animal per week), increased after the onset of the first scattered rains, reached a peak (40 ticks per animal per week) 1 month after the beginning of the heavy rains, and declined thereafter. The dominant tick species was Amblyomma variegatum; other species found were Boophilus spp., Rhipicephalus spand Hyalomma spThe low level of tick load compared with data from literature and from crossbred (Friesian-Bunaji)cattle kept in the study area suggests high tick resistance in Bunaji cattle. A biologically feasible method of controlling ticks in indigenous cattle would be twice weekly spraying with acaricide during only 2 months of the year in the early wet season to break the pronounced peak in the tick load. However, hand spraying offers on advantage over hand removal of ticks in terms of saving labour. The main advantage of strategic spraying lies in more thorough removal of ticks and possibly prevention of dermatophilosis at a lower cost than year-round use of acaricide. Knowledge of the seasonal pattern of tick load is also valuable for planning the introduction of selected stock with higher genetic potential, but higher susceptibility to tick-borne diseases than exhibited by Bunaji cattle.